HEALTHCARE WASTE MANAGEMENT IN PUNJAB, INDIA: CURRENT PRACTICES, CHALLENGES AND RECOMMENDATIONS - Musaib Gul (Universitas Efarina, 2022)
Abstract Healthcare waste management is an essential component of both public health and environmental sustainability. The purpose of this study article is to evaluate present practises, difficulties, and recommendations for healthcare waste management in Punjab, India. While Punjab has made progress in implementing waste management legislation, the analysis finds that there are still severe gaps in infrastructure, training, and awareness. Inadequate segregation, ineffective disposal methods, and a lack of resources all impede effective healthcare waste management. Recommendations for addressing these concerns include strengthening regulatory frameworks, increasing infrastructure and technology, improving training and awareness programmes, and fostering research and innovation.